2019
DOI: 10.1001/jamanetworkopen.2019.11838
|View full text |Cite
|
Sign up to set email alerts
|

Association of Early-Stage Breast Cancer and Subsequent Chemotherapy With Risk of Atrial Fibrillation

Abstract: This matched cohort study investigates whether early-stage breast cancer and subsequent chemotherapy are associated with the risk of developing atrial fibrillation among women in Ontario, Canada, who were diagnosed with early-stage breast cancer compared with women without breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
2
22
3
Order By: Relevance
“…Not all studies are in agreement with this correlation: a population-based, retrospective, matched cohort study suggests that women patients with early breast cancer may not have a higher prevalence of AF before cancer diagnosis [ 28 ]. However, such observation should be interpreted with caution since the prevalence of CVD and its risk factors is well known to be lower in women population.…”
Section: Atrial Fibrillation In Cancermentioning
confidence: 99%
“…Not all studies are in agreement with this correlation: a population-based, retrospective, matched cohort study suggests that women patients with early breast cancer may not have a higher prevalence of AF before cancer diagnosis [ 28 ]. However, such observation should be interpreted with caution since the prevalence of CVD and its risk factors is well known to be lower in women population.…”
Section: Atrial Fibrillation In Cancermentioning
confidence: 99%
“…Besides linear models, the deep learning method is also used to predict complications of this chronic disease [20] but this work considers each complication independently. For breast cancer survivors, relationships between cardiac complications and cancer were also investigated [3], [4], [21] to show the correlation between these two diseases.…”
Section: Related Workmentioning
confidence: 99%
“…In our setting, we focus on profiling the risk of developing cardiac complications in a six-month window after the initial diagnosis of breast cancer, and the positive instances are defined as patients who have cardiac complications in this window. Following previous clinical research [3], [4], we identify six cardiac complications including atrial fibrillation (AF), coronary artery disease (CAD), heart failure (HF), hypertension, peripheral arterial disease (PAD), and stroke. Descriptions, ICD codes, and the corresponding numbers of positive instances of these complications are shown in Table II.…”
Section: A Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, while numerous studies have suggested a higher risk of cancer following an AF diagnosis [ 15 ] with a significant prevalence of colorectal cancer [ 16 ], there is a paucity of research in the literature focusing on AF in patients with preexisting BC [ 17 ]. In addition, despite the well-known cardiotoxic side effects of treatments frequently used in BC [ 18 , 19 , 20 ], including radiotherapy [ 10 ], little is known whether cardiotoxic chemotherapy may enhance the link between BC and AF [ 5 , 21 ]. Finally, the higher risk of AF has been more commonly reported in the early stage of the disease [ 22 ], whereas AF associated with metastatic breast cancer (MBC) has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%